Characterization of the Network Structure of PEG Diacrylate Hydrogels Formed in the Presence of N‐Vinyl Pyrrolidone. Issue 4 (15th November 2013) - Lee, Chu‐Yi; Teymour, Fouad; Camastral, Heinz; Tirelli, Nicola; Hubbell, Jeffrey A.; Elbert, Donald L.; Papavasiliou, Georgia; Pinto, José Carlos
Abstract PEGDA hydrogels copolymerized with NVP using free‐radical photopolymerization are used in biomedical applications. These networks consist of a poly(acrylate‐co‐vinyl pyrrolidone) backbone crosslinked with PEG chains whose crosslink density is dependent on the backbone molecular weight and composition. Insight into the network structure and characterization of the backbone molecular weight and composition is achieved by considering hydrogel degradation through ester bond hydrolysis resulting in the release of PEG and poly(acrylic acid‐co‐vinyl pyrrolidone). A model is developed to determine the influence of kinetic constants and phenomena on the backbone formation and is compared to experimental data. Results indicate that the backbone molecular weight is related to the amount of NVP and unaffected by polymerization time.<inline-graphic xlink:href="ark:/27927/pgg59wdgvr3" content-type="mren201300166-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />